Efektivitas Undang–Undang Nomor 20 Tahun 2016 tentang Merek Berkaitan dengan Perlindungan Hukum terhadap Kain Tenun Rangrang di Desa Pejukutan Nusa Penida - I Kadek Heri Diana S; Nella Hasibuan OLeary; Ida Ayu Puru Widiati (Warmadewa Press, 2021)
Nusa Penida is very well known for its rangrang woven cloth, but until now the filing of the cloth brand to the Directorate General of Intellectual Property has not been realized as a form of legal protection. The purpose of this research is to reveal the effectiveness of law number 20 of 2016 concerning the brand on rangrang woven fabrics in the Village of Nusa Penida and the efforts to protect the law against the woven cloth rangrang in the Village of Nusa Penida. The research method used is empirical. Primary data and secondary data were obtained by conducting observations and interviews as well as literature. Based on the results of research obtained by Law Number 20 of 2016 concerning brands, it cannot be said to be effective because the community does not register the woven woven cloth at the Directorate General of Intellectual Property, this is due to the lack of citizen knowledge of the law. So that government efforts are needed to provide socialization related to the importance of registering rangrang woven fabrics. And efforts to protect rangrang woven fabrics are still in the registration process and there will be socialization and services as well as assistance from the government for the smooth registration of rangrang woven fabrics at the Directorate General of Intellectual Property.